Some aspects of experimental hemorrhagic shock - Zapata Ortiz, Vicente (1956)
Although hemorrhagic shock has been studied extensively, the cause of the fatal outcome, as well as other forms of shock, has not been fully established. Our aim was, first, to know the mechanism of the protective action of chlorpromazine, but at the same time have believed that their research could perhaps shed some light on the explanation of the phenomenon of irreversibility. In addition, we wanted to know if this drug may be active after the shock has been installed, either by administering it alone, or accompanied by blood transfusion, which, besides being of great practical importance could have theoretical implications of interest.